Production of a monoclonal antibody to Vibrio cholerae non-O1 heat-stable enterotoxin (ST) which is cross-reactive with Yersinia enterocolitica ST. - Takeda, T (1990)
A monoclonal antibody (MAb) against synthetic heat-stable enterotoxin of Vibrio cholerae non-O1 (NAG-ST) was produced. The MAb, namely, 2F, belonged to the immunoglobulin G1 class. Ascitic fluid drawn from pristane-primed BALB/c mice injected with a 2F-producing clone demonstrated anti-NAG-ST activity which could be detected in enzyme-linked immunosorbent assay even at a dilution of 1:128,000. Fifty-fold-diluted ascitic fluid could completely neutralize the activity of NAG-ST (synthetic and native) and Vibrio mimicus ST (identical to NAG-ST) in suckling mice. In the same assay, 2F could also neutralize Yersinia enterocolitica ST (Y-ST) but did not neutralize Escherichia coli STh and STp. A similar pattern of reactivity occurred in a competitive enzyme-linked immunosorbent assay with homologous and heterologous toxins. Competitive inhibition curves with synthetic peptides representing NAG-ST and its shorter analogs revealed that aspartic acid located at position 2 from the N terminus of NAG-ST was the essential residue of the recognized epitope. Significantly, in Y-ST, to which 2F cross-reacted, aspartic acid is in the corresponding position as that of NAG-ST, thereby confirming our conclusions that the epitope defining this MAb is aspartic acid.